Does drinking coffe accelerate the development of heart failure? (Journal of Universal Science Research, 2023)
coffee is the second most consumed drink in the world after water, and it is consumed by healthy and sick people from 7 to 70 years old. One of the ingredients in coffee, cocaine, has been found to have a negative effect on the cardiovascular system in several studies.  in order to expand these results, this article covers the research conducted in order to study the effect of coffee on heart failure in elderly people with advanced heart failure. Scientists are still working on coffe it’s benefits and risks for health.Data also found that drinking coffe a lot was associated with more development of heart failure.